Efektivitas Bahan Ajar Sejarah Interaktif Berbasis Kearifan Lokal Untuk Meningkatkan Pemahaman Budaya Siswa - Apdelmi; Sutimin, Laeo Agung; Djono (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The development of technology as a result of globalization has eroded many cultural attitudes and behaviors in today's millennial society. The lack of involvement of the younger generation in local culture and interest in local cultural history is feared to erode cultural identity. Local wisdom will eventually be marginalized by modern culture and endangered. Cultural understanding in the younger generation can be started from strengthening local wisdom in the education system, one of which is in history teaching materials. The purpose of this study was to test the effectiveness of interactive History teaching materials based on local wisdom to improve the cultural understanding of high school students in Kerinci Regency. The data collection techniques used were observation, questionnaire and written test. The results showed that the interactive History teaching materials were able to improve students' cultural understanding. obtained a significance value (p-value) of 0.001 and 0.000, which are both smaller than the significant level of 0.05 (0.001 < 0.05 and 0.000 < 0.05). These results indicate that there is a significant difference in students' understanding of local wisdom between the experimental class using interactive history teaching materials based on local wisdom and the control class using printed books at school.